A method for preparing a high specific capacity composite anode foil and an aluminum electrolytic capacitor
Patent Information
- Application Number
- CN202611165642.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-23
AI Technical Summary
[0003]而积层箔是采用 3~8μm的铝粉浆料单面或双面涂覆在光箔上,然后在600℃以上高温烧结而成;浆料含有机粘结剂,烧结后残碳偏高,直接导致电容器漏电流增大
[0024]与现有技术相比,本发明的优点在于:在本发明中,通过3D打印技术直接将铝粉或者铝合金粉直接冶金结合在腐蚀箔上,这样在阳极箔表面实现梯度孔径;由于基箔采用了腐蚀箔,故比容能够提高20%-35%。
Abstract
Description
Technical Field
[0001] This invention relates to an anode foil for aluminum electrolytic capacitors, and more particularly to a method for preparing a high-specific-capacitance composite anode foil. Background Technology
[0002] Currently, the anode foils used in aluminum electrolytic capacitors are mainly etched foils and multilayer foils. Electrochemically etched foils rely solely on tunnel corrosion of the aluminum foil substrate to increase the specific surface area, but the increase in specific capacitance is nearing its theoretical limit; furthermore, the etching process generates a large amount of acidic waste liquid, resulting in high environmental treatment costs. To further increase the specific capacitance of the anode foil, multilayer foils are now available on the market.
[0003] Laminated foil is made by coating one or both sides of a 3-8μm aluminum powder paste onto a bright foil, and then sintering it at a high temperature above 600℃. The paste contains organic binders, resulting in a high residual carbon content after sintering, which directly leads to an increase in capacitor leakage current. In addition, because it needs to withstand a high temperature of over 600 degrees Celsius, the base foil can only be a bright foil, that is, an unetched aluminum foil. Summary of the Invention
[0004] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a method for preparing high specific capacitance composite anode foil and an aluminum electrolytic capacitor.
[0005] To solve the above-mentioned technical problems, the technical solution proposed by this invention is: a method for preparing a high specific capacity composite anode foil, comprising the following steps:
[0006] 1) Pre-treat the etched foil used as the base foil;
[0007] 2) Place the pretreated base foil into the 3D cold spray oxygen-free chamber;
[0008] 3) 3D printing;
[0009] 3.1) Preheat the base foil to 120-160℃ in the oxygen-free cavity of the 3D cold spray coating process;
[0010] 3.2) Using a 3D additive cold spray gun in an inert atmosphere, aluminum powder or aluminum alloy powder with a diameter of 1-10 μm is sprayed onto the base foil to achieve mechanical interlocking and / or metallurgical bonding to form an additive porous layer, thus obtaining the anode foil precursor; the driving gas of the 3D additive cold spray gun includes high-purity industrial N2, the spraying pressure is between 2.6-3.2 MPa, the temperature of the driving gas in the 3D additive cold spray gun is between 420-500℃, the spraying distance between the 3D additive cold spray gun and the base foil is between 15-22 mm, and the powder feeding rate of the 3D additive cold spray gun is between 15-50 g / min;
[0011] 4) The anode foil precursor obtained in step 3) is vacuum annealed at 380-450℃ for 1-5 hours;
[0012] 5) The anode foil precursor processed in step 4) is converted into a high specific capacity composite anode foil.
[0013] In the preferred method for preparing the high specific capacity composite anode foil described above, after completing the pretreatment in step 1), the base foil is placed into the 3D cold spray oxygen-free cavity within 1 hour.
[0014] In the above-mentioned method for preparing high specific capacity composite anode foil, preferably, the oxygen content in the 3D cold spray oxygen-free cavity is less than 100 ppm.
[0015] In the above-described method for preparing high specific capacity composite anode foil, preferably, the vacuum degree in step 4) is less than 5 × 10⁻⁶. - 3 Pa.
[0016] In the above-mentioned method for preparing high specific capacity composite anode foil, preferably, the thickness of the etched foil is between 80-120 μm.
[0017] In the above-mentioned method for preparing high specific capacity composite anode foil, preferably, the thickness of the additive porous layer is 10-60 μm, and the pore size of the additive porous layer is 1-1.5 μm.
[0018] In the above-mentioned method for preparing high specific capacity composite anode foil, preferably, the additive porous layer in step 3) is formed by spraying aluminum powder or aluminum alloy powder onto the base foil twice using a 3D additive cold spray gun; the diameter of the aluminum powder or aluminum alloy powder sprayed onto the base foil for the first time by the 3D additive cold spray gun is 1-5 μm, and the diameter of the aluminum powder or aluminum alloy powder sprayed for the second time is 3-10 μm.
[0019] The above-mentioned method for preparing high specific capacity composite anode foil, preferably, includes the following pretreatment steps in step 1):
[0020] 1.1) Immerse the base foil in an organic solvent and ultrasonically clean for at least 15 minutes;
[0021] 1.2) Immerse the base foil treated in step 1.1) in a 1-10 g / L NaOH solution for 5-20 seconds, then rinse it with deionized water.
[0022] In the preferred method for preparing the high specific capacity composite anode foil described above, plasma treatment is performed after the base foil has completed step 1.2); argon or argon-hydrogen mixed gas is used as the working gas source, the vacuum degree is controlled at 0.5-5 Pa, the radio frequency power is 100-300 W, and the treatment time is 60-180 s.
[0023] An aluminum electrolytic capacitor includes an anode foil prepared by the above-described method for preparing high-specific-capacitance composite anode foil.
[0024] Compared with the prior art, the advantages of the present invention are as follows: In the present invention, aluminum powder or aluminum alloy powder is directly metallurgically bonded to the etched foil by 3D printing technology, thus achieving a gradient aperture on the surface of the anode foil; since the base foil is an etched foil, the specific volume can be increased by 20%-35%. Detailed Implementation
[0025] To facilitate understanding of the present invention, the present invention will be described more fully and in detail below with reference to preferred embodiments, but the scope of protection of the present invention is not limited to the following specific embodiments.
[0026] It should be noted that when a component is described as being "fixed to, attached to, connected to or connected to" another component, it can be directly fixed to, attached to, connected to or connected to the other component, or it can be indirectly fixed to, attached to, connected to or connected to the other component through other intermediate connectors.
[0027] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.
[0028] Example 1
[0029] A method for preparing a high specific capacity composite anode foil, characterized by comprising the following steps:
[0030] 1) Pre-treatment of the etched foil used as the base foil; specifically including the following steps:
[0031] 1.1) The base foil is immersed in an organic solvent and ultrasonically cleaned for at least 15 minutes. In this embodiment, the base foil is first ultrasonically cleaned in acetone for 15 minutes, then ultrasonically cleaned in anhydrous ethanol for 15 minutes, and then immediately dried with N2 gas. Acetone has excellent non-polar oil-dissolving ability, and anhydrous ethanol can replace residual acetone and further clean the surface of the base foil; after cleaning, it is immediately dried with high-purity inert gas to reduce the risk of solvent and moisture residue and secondary oxidation of the aluminum foil surface.
[0032] 1.2) Immerse the substrate foil treated in step 1.1) in a 1-10 g / L NaOH solution for 5-20 seconds, then rinse thoroughly with deionized water. In this embodiment, the substrate foil cleaned in step 1.1) is briefly immersed in a 1-10 g / L sodium hydroxide solution for 5-20 seconds. The weak alkaline solution reacts with the natural alumina passivation film on the aluminum surface to generate soluble sodium aluminate, effectively stripping the oxide barrier layer and exposing the aluminum substrate. Simultaneously, the weak alkaline solution produces slight micro-etching on the aluminum substrate, creating a micro-uneven surface morphology, which is beneficial for improving the interfacial bonding effect after impact of cold-sprayed aluminum powder or aluminum alloy powder particles. After immersion in the weak alkaline solution, immediately rinse thoroughly with deionized water to remove residual NaOH and reaction products, avoiding impurity residue. In this invention, it is necessary to strictly control the alkaline concentration and immersion time to prevent excessive corrosion that could damage the original tunnel corrosion blind hole structure of the substrate.
[0033] In this embodiment, the thickness of the etched foil is between 80-120 μm, and it has tunnel blind holes with a pore size of 0.8-1.3 μm etched inside.
[0034] 1.3) After the base foil completes step 1.2), plasma treatment is performed; argon or argon-hydrogen mixture is used as the working gas source, the vacuum degree is controlled at 0.5-5Pa, the radio frequency power is 100-300W, and the treatment time is 60-180s.
[0035] In this embodiment, high-energy ion physical sputtering is used to thin and break down the original oxide film on the surface of the etched foil, creating interface defects on the foil surface. Simultaneously, surface-adsorbed contaminants are removed, enhancing the surface activity of the aluminum foil. After plasma treatment, the base foil is directly transferred to a 3D cold spray oxygen-free chamber for aluminum powder additive porous layer spraying, preventing re-oxidation of the fresh aluminum surface.
[0036] 2) Place the pretreated base foil into the 3D cold spray oxygen-free chamber. After completing step 1), place the base foil into the 3D cold spray oxygen-free chamber within 1 hour; preferably, place the pretreated base foil into the 3D cold spray oxygen-free chamber within 20 minutes. In this embodiment, the oxygen content in the 3D cold spray oxygen-free chamber is less than 100 ppm.
[0037] 3) 3D printing;
[0038] 3.1) Preheat the base foil to 120-160℃ in the oxygen-free cavity of the 3D cold spray coating process;
[0039] 3.2) Using a 3D additive cold spray gun in an inert atmosphere, aluminum powder or aluminum alloy powder with a diameter of 1-10 μm is sprayed onto a base foil to achieve mechanical bonding and / or metallurgical bonding, forming an additive porous layer to obtain the anode foil precursor. In this embodiment, the driving gas of the 3D additive cold spray gun includes high-purity industrial N2, the spraying pressure is between 2.6-3.2 MPa, the temperature of the driving gas inside the 3D additive cold spray gun is between 420-500℃, the spraying distance between the 3D additive cold spray gun and the base foil is between 15-22 mm, and the powder feed rate of the 3D additive cold spray gun is between 15-50 g / min. In this embodiment, the thickness of the additive porous layer is between 10-60 μm; the pore size of the additive porous layer is between 1-1.5 μm. The inert atmosphere can be nitrogen or argon.
[0040] In this embodiment, in step 3.2), after the aluminum powder or aluminum alloy powder particles are sprayed from the 3D additive cold spray gun, they impact the base foil and adjacent powder particles at a temperature of 420-500°C. During this process, the particles undergo intense plastic rheology, breaking through the surface oxide film and interlocking, hooking, and meshing to form a physical interlocking. Simultaneously, at 420-500°C, the aluminum powder or aluminum alloy powder undergoes high-speed impact, breaking down its own oxide film, that of adjacent powder particles, and the surface of the corroded foil. This achieves atomic exchange between the powder and the substrate, as well as between powder particles themselves, resulting in a dual anchoring of physical interlocking and metallurgical bonding.
[0041] 4) The anode foil precursor obtained in step 3) is vacuum annealed at 380-450℃ for 1-5 hours; in this embodiment, the vacuum degree is less than 5×10⁻⁶. -3 Pa. In this embodiment, residual stress is released during annealing; at the same time, slight interfacial diffusion occurs at the sites where metallurgical bonding previously occurred between aluminum powder or aluminum alloy powder, and between aluminum powder or aluminum alloy powder and base foil, slightly widening the original metallurgical bonding area.
[0042] 5) The anode foil precursor processed in step 4) is converted into a high specific capacity composite anode foil.
[0043] In this embodiment, aluminum powder or aluminum alloy powder is directly metallurgically bonded to the etched foil using 3D printing technology, thus achieving a gradient aperture on the surface of the anode foil; since the base foil is an etched foil, the specific volume can be increased by 20%-35%.
[0044] Example 2
[0045] In this embodiment, the additive porous layer in step 3) is formed by spraying aluminum powder or aluminum alloy powder onto the base foil twice using a 3D additive cold spray gun; the diameter of the aluminum powder or aluminum alloy powder sprayed onto the base foil for the first time by the 3D additive cold spray gun is 1-5μm, and the diameter of the aluminum powder or aluminum alloy powder sprayed for the second time is 3-10μm.
[0046] In this embodiment, the first layer adjacent to the base foil uses 1-5 μm aluminum powder or aluminum alloy powder, while the surface layer uses 3-10 μm aluminum powder or aluminum alloy powder. The fine 1-5 μm powder in the first layer more easily reaches the critical impact velocity required to form an interface bond with the base foil, and the plastic deformation during impact is more complete, forming a dense and continuous metallurgical transition layer on the surface of the base foil, strengthening the interface bond between the powder and the corrosion foil, and ensuring the continuity of the conductive path. The relatively coarser 3-10 μm powder in the surface layer, after being bonded to the first layer, forms a porous outer layer with higher porosity and interconnection. The gradient pore structure of this embodiment achieves the structural characteristics of a dense and conductive inner layer and a loose and porous outer layer. The interconnected pores in the surface layer can serve as electrolyte transport channels, alleviating the problem of pore blockage during the anodizing formation stage, improving the effective utilization rate of micropores inside the porous layer, and increasing the effective specific surface area of the composite anode foil while ensuring the interface bonding strength and low contact resistance. At the same time, the gradient pore distribution can alleviate the residual stress inside the coating and improve the coating's resistance to cracking and peeling.
[0047] The other parts of this embodiment are the same as those in Embodiment 1.
[0048] Comparative Example 1
[0049] Compared with Example 1, Comparative Example 1 uses aluminum powder or aluminum alloy powder of the same particle size for sintering; the process adopts the method of CN110828183A.
[0050] The anode foils of Examples 1, 2, and 1 were all formed using a 520V DC multi-stage formation process. Subsequently, specific capacitance tests were performed. The specific capacitance of the anode foil of Comparative Example 1 was about 0.8 μF / cm², while the specific capacitance of the anode foils of Examples 1 and 2 was about 0.97 μF / cm².
Claims
1. A method for preparing a high specific capacity composite anode foil, characterized in that, Includes the following steps: 1) Pre-treat the etched foil used as the base foil; 2) Place the pretreated base foil into the 3D cold spray oxygen-free chamber; 3) 3D printing; 3.1) Preheat the base foil to 120-160℃ in the oxygen-free cavity of the 3D cold spray coating process; 3.2) Using a 3D additive cold spray gun in an inert atmosphere, aluminum powder or aluminum alloy powder with a diameter of 1-10 μm is sprayed onto the base foil to achieve mechanical interlocking and / or metallurgical bonding to form an additive porous layer, thus obtaining the anode foil precursor; the driving gas of the 3D additive cold spray gun includes high-purity industrial N2, the spraying pressure is between 2.6-3.2 MPa, the temperature of the driving gas in the 3D additive cold spray gun is between 420-500℃, the spraying distance between the 3D additive cold spray gun and the base foil is between 15-22 mm, and the powder feeding rate of the 3D additive cold spray gun is between 15-50 g / min; 4) The anode foil precursor obtained in step 3) is vacuum annealed at 380-450℃ for 1-5 hours; 5) The anode foil precursor processed in step 4) is converted into a high specific capacity composite anode foil.
2. The method for preparing high specific capacity composite anode foil according to claim 1, characterized in that: Step 1) After completing the pretreatment, place the base foil into the 3D cold spray oxygen-free cavity within 1 hour.
3. The method for preparing high specific capacity composite anode foil according to claim 1, characterized in that: The oxygen content in the oxygen-free cavity of the 3D cold spray coating is less than 100 ppm.
4. The method for preparing high specific capacity composite anode foil according to claim 1, characterized in that: In step 4), the vacuum level is less than 5 × 10⁻⁶. -3 Pa.
5. The method for preparing high specific capacity composite anode foil according to claim 1, characterized in that: The thickness of the etched foil is between 80-120 μm.
6. The method for preparing high specific capacity composite anode foil according to claim 1, characterized in that: The thickness of the additive porous layer is 10-60 μm; the pore size of the additive porous layer is 1-1.5 μm.
7. The method for preparing high specific capacity composite anode foil according to any one of claims 1-6, characterized in that: The additive porous layer in step 3) is formed by spraying aluminum powder or aluminum alloy powder onto the base foil twice using a 3D additive cold spray gun; the diameter of the aluminum powder or aluminum alloy powder sprayed onto the base foil for the first time by the 3D additive cold spray gun is 1-5μm, and the diameter of the aluminum powder or aluminum alloy powder sprayed for the second time is 3-10μm.
8. The method for preparing high specific capacity composite anode foil according to any one of claims 1-6, characterized in that, The preprocessing in step 1) includes the following steps: 1.1) Immerse the base foil in an organic solvent and ultrasonically clean for at least 15 minutes; 1.2) Immerse the base foil treated in step 1.1) in a 1-10 g / L NaOH solution for 5-20 seconds, then rinse it with deionized water.
9. The method for preparing high specific capacity composite anode foil according to claim 8, characterized in that: After completing steps 1 and 2) on the base foil, plasma treatment is performed; argon or argon-hydrogen mixture is used as the working gas source, the vacuum degree is controlled at 0.5-5Pa, the radio frequency power is 100-300W, and the treatment time is 60-180s.
10. An aluminum electrolytic capacitor, characterized in that: The anode foil prepared by the method for preparing high specific capacity composite anode foil according to any one of claims 1-9.
Citation Information
Patent Citations
Manufacturing method of aluminum electrolytic capacitor anode foil based on sintered aluminum and capacitor
CN110828183A